SOROCABANA 2014: PAISAGEM SONORA ENATIVA COMO INTERVENÇÃO ESTÉTICA - André Luiz Gonçalves de Oliveira; Felipe Fachiolli Pedro (Universidade do Oeste Paulista, 2015)
The Enactive Soundscapes were developed from studies of perception by enactive approach of cognitive science and its application to procedures of Soundscape composition. This paper presents the realization of an urban intervention, "Sorocabana 2014," as an example of application in enactive perspective of Soundscape creation. We show the context of Soundscapes as used to apply the knowledge derived from studies in perception, through its roots in eletroacoustic music, and the way of canadian composers of Simon Fraser University comprehend and use it. Later stages of implementing "Sorocabana 2014", while results of enactives ideas applied to the composition of Soundscapes were described. Finally we made a brief discussion on the proposal to subsidize artistic production with the enactive approach to perception. And as a conclusion it is stressed some other possibilities of aesthetic creation involving such philosophical-scientific scope.